Long-term Services and Supports and Disease Management among Older Chinese Adults in Different Stages of Cognitive Impairment - Zhuoer Lin; Xi Chen (Global Labor Organization (GLO), 2022)
Rapid population aging elevates burden of chronic and non-communicable diseases among older adults. Despite the critical role of self-management in disease prevention and control, effective management of diseases can be cognitively demanding and may require additional supports from family and social services. Using nationally representative data from China, this paper reveals great challenges in disease management and characterizes the differential effects of long-term care services and supports (LTSS) on disease management among older adults in different stages of cognitive impairment (CI). In specific, we use preventive care utilization and hypertension management as key indicators to assess the performance of disease management. We show that while access to LTSS from spouse or home-based services significantly facilitate active disease management behaviors, the effects are only evident among older adults with no CI. By contrast, access to LTSS has very modest effect for cognitively impaired individuals. In addition, older adults in more severe stages of CI perform worse in disease prevention, hypertension awareness and management. These findings reveal the vulnerability of older adults with CI in disease management and point to the importance of promoting targeted interventions to reduce barriers of accessing LTSS, especially among cognitively impaired population.
Keywords: 330; Long-term Services and Supports; Chronic Disease Management; Cognitive Impairment; Preventive Care Utilization; Disease Awareness; Hypertension